Improving the Performance of Shallow Footing Subjected to Uplift Loading Using Structural Skirt - Al-Zubaidi, Aqeel J.; Al-Saidi, A’amal A. H. (Salehan Institute of Higher Education, 2025)
The increasing demand for internet and phone services had required the construction of transmission towers in various terrains, including loose sand, which was often found in desert areas and exposed to wind loads that can pull out these towers. This study aims to improve the uplift resistance of shallow footings subjected to pure uplift forces. In this research, a loading system with a data logger, a shallow footing model, and skirts with different shapes, lengths, and inclination angles was used. The performance and behavior of unskirted footing resting on loose sand with 30% relative density were analyzed and compared with skirted footing under uplift loads. The results showed that increasing the L/B (where L is the footing length and B is the footing width) up to 2 and the inclination angles up to 45° of the skirt gave a significant increase in uplift resistance for skirts with straight corners by 26 times and 19 times for chamfered corners, compared with unskirted footing. It is noted that increasing L/B has less effect than increasing inclination angles by recording 6 times with L=2B and 0°. Skirt footing with straight corners demonstrates better performance than chamfered corners.